2016
DOI: 10.7554/elife.18432
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of allosteric regulation of β2-adrenergic receptor by cholesterol

Abstract: There is evidence that lipids can be allosteric regulators of membrane protein structure and activation. However, there are no data showing how exactly the regulation emerges from specific lipid-protein interactions. Here we show in atomistic detail how the human β2-adrenergic receptor (β2AR) – a prototypical G protein-coupled receptor – is modulated by cholesterol in an allosteric fashion. Extensive atomistic simulations show that cholesterol regulates β2AR by limiting its conformational variability. The mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
149
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(178 citation statements)
references
References 68 publications
13
149
0
Order By: Relevance
“…Molecular dynamics (MD) simulations have provided structural insights into GPCR-lipid interactions. Atomistic simulations identified multiple cholesterol binding sites on the surface of GPCRs, the occupancy of which resulted in increased conformational stability (Guixa-Gonzalez et al, 2017;Lyman et al, 2009;Manna et al, 2016). Frequent insertion of PG into the opening between TM6 and TM7 was observed in atomistic simulations of b2 adrenergic receptor in the active state conformation, suggesting a possible explanation for the influence of anionic lipids on GPCR activation (Neale et al, 2015).…”
Section: Introductionmentioning
confidence: 94%
“…Molecular dynamics (MD) simulations have provided structural insights into GPCR-lipid interactions. Atomistic simulations identified multiple cholesterol binding sites on the surface of GPCRs, the occupancy of which resulted in increased conformational stability (Guixa-Gonzalez et al, 2017;Lyman et al, 2009;Manna et al, 2016). Frequent insertion of PG into the opening between TM6 and TM7 was observed in atomistic simulations of b2 adrenergic receptor in the active state conformation, suggesting a possible explanation for the influence of anionic lipids on GPCR activation (Neale et al, 2015).…”
Section: Introductionmentioning
confidence: 94%
“…GPCRs constitute one of the largest classes of membrane proteins, and their key roles in many biological processes mean that they make up approximately one-third of all drug targets [58]. Many GPCRs have been shown to bind [59,60] and have been suggested to be functionally modulated by cholesterol [61][62][63]. These include the intensively studied adenosine 2A (A 2A R) and β2-adrenergic (β-2AR) receptors.…”
Section: Binding Of Cholesterol To Gpcrs and Other Membrane Proteinsmentioning
confidence: 99%
“…For example, a crystal structure of the Class A GPCR β2-adrenegic receptor identified cholesterol bound to the intracellular region of TM4 (23), which was validated by observation of cholesterol binding to the same binding site in MD simulations (24). MD simulations have shown how cholesterol binding can modulate the conformation dynamics of the β2 adrenergic receptor (25). MD simulations have also demonstrated that phosphatidylinositol (4,5)-bisphosphate (PIP2) binds more favourably to active than to inactive states of the adenosine 2A receptor thus favouring receptor activation (26).…”
Section: Introductionmentioning
confidence: 88%